2014
DOI: 10.1016/j.scr.2013.09.006
|View full text |Cite
|
Sign up to set email alerts
|

HIF1α is a regulator of hematopoietic progenitor and stem cell development in hypoxic sites of the mouse embryo

Abstract: Hypoxia affects many physiologic processes during early stages of mammalian ontogeny, particularly placental and vascular development. In the adult, the hypoxic bone marrow microenvironment plays a role in regulating hematopoietic stem cell (HSC) function. HSCs are generated from the major vasculature of the embryo, but whether the hypoxic response affects the generation of these HSCs is as yet unknown. Here we examined whether Hypoxia Inducible Factor1-alpha (HIF1α), a key modulator of the response to hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 34 publications
(50 reference statements)
7
68
0
Order By: Relevance
“…A recent study also observed hypoxia in the FL, 15 and ours is the first description of a role for HIF signaling in the survival of FL HSCs. Given the previously described role for hypoxia in yolk sac, 16 AGM, 18 and BM HSCs, 21 we propose that hypoxia-and O 2 -sensitive factors represent universal regulators of hematopoietic progenitor cells.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A recent study also observed hypoxia in the FL, 15 and ours is the first description of a role for HIF signaling in the survival of FL HSCs. Given the previously described role for hypoxia in yolk sac, 16 AGM, 18 and BM HSCs, 21 we propose that hypoxia-and O 2 -sensitive factors represent universal regulators of hematopoietic progenitor cells.…”
Section: Discussionsupporting
confidence: 73%
“…5,6,15 Embryoid bodies generated in vitro from Arntdeficient mouse embryonic stem cells form fewer hematopoietic colonies, suggesting that hypoxia promotes formation of early hematopoietic cells. 16,17 Consistently, germline Arnt deletion results in diminished numbers of yolk sac hematopoietic progenitors, demonstrating that HIF is critical for hematopoietic development.…”
mentioning
confidence: 99%
“…In spite of the hyper-vascularity of the bone marrow cavity, the oxygen tension is as low as in venous blood, owing to high levels of oxygen consumption by the proliferating HSPCs (Nombela-Arrieta, Pivarnik et al 2013). Conditional knock-out of the Hif1α gene leads to increased levels of reactive oxygen species (ROS) in HSPCs and depletion of the cells, which suggests that HIF1α is indispensable for stem cell function in the hematopoietic system (Imanirad, Solaimani Kartalaei et al 2014). In addition, studies have shown that HSPCs are generally quiescent cells that are sensitive to intracellular ROS (Orkin and Zon 2008).…”
Section: Er Stress Angiogenic Progenitor Cells and Vascular Repairmentioning
confidence: 99%
“…Other physicochemical parameters include proteolytic matrix remodeling and matrix stiffness, which affect vascular morphogenesis and network formation Busnadiego et al, 2013;Turturro et al, 2013). Oxygen availability has also been shown to play a crucial role in early vascular development (Imanirad et al, 2014). This range of physicochemical properties that regulate vascular development in vivo represents the many variables that must be considered for vascular engineering and regeneration approaches.…”
Section: Vascular Development and Engineering Parametersmentioning
confidence: 99%